2019
DOI: 10.1101/gr.230243.117
|View full text |Cite
|
Sign up to set email alerts
|

An AR-ERG transcriptional signature defined by long-range chromatin interactomes in prostate cancer cells

Abstract: The aberrant activities of transcription factors such as the androgen receptor (AR) underpin prostate cancer development. While the AR cis-regulation has been extensively studied in prostate cancer, information pertaining to the spatial architecture of the AR transcriptional circuitry remains limited. In this paper, we propose a novel framework to profile long-range chromatin interactions associated with AR and its collaborative transcription factor, erythroblast transformation-specific related gene (ERG), usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 63 publications
3
59
0
Order By: Relevance
“…Specifically, we found that ERG stimulates AR binding to high affinity palindromic ARE DNA consensus sites, as well as lower affinity ARE half sites, independent of an ETS consensus motif. The optimal 6-to 7-base pair spacing between AR and ETS binding sites that we observed on AR-ERG codependent genes in cells and in our synthetic dsDNA templates is intriguing and invokes at least two possible models: 1) that DNA can assist in orienting the two proteins for subsequent protein-protein interaction, and 2) that ERG can stimulate AR's binding to DNA independent of ERG's own DNA binding, consistent with recent evidence suggesting that AR and ERG form long-range interactions through chromosomal looping (55). Our biochemical observations also provide insight to previous findings in cancer cells that ERG amplification expands the AR cistrome to genes that otherwise have low AR occupancy (18)(19)(20), and that ETS factors can modulate AR binding to DNA when AR is otherwise impaired (Figs.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, we found that ERG stimulates AR binding to high affinity palindromic ARE DNA consensus sites, as well as lower affinity ARE half sites, independent of an ETS consensus motif. The optimal 6-to 7-base pair spacing between AR and ETS binding sites that we observed on AR-ERG codependent genes in cells and in our synthetic dsDNA templates is intriguing and invokes at least two possible models: 1) that DNA can assist in orienting the two proteins for subsequent protein-protein interaction, and 2) that ERG can stimulate AR's binding to DNA independent of ERG's own DNA binding, consistent with recent evidence suggesting that AR and ERG form long-range interactions through chromosomal looping (55). Our biochemical observations also provide insight to previous findings in cancer cells that ERG amplification expands the AR cistrome to genes that otherwise have low AR occupancy (18)(19)(20), and that ETS factors can modulate AR binding to DNA when AR is otherwise impaired (Figs.…”
Section: Discussionsupporting
confidence: 86%
“…Similar associations have been observed for GWAS identified genomic loci with the risk of ERnegative disease in breast cancer subtypes [54]. Further, functional analysis based on long range chromatin interactomes analysis in CaP cells has shown strong enrichment of CaP GWAS SNPs at AR-ERG co-binding sites participating in chromatin interactions and gene regulation, suggesting potential functional role of these SNPs towards specific ERG subtype [55].…”
Section: Discussionsupporting
confidence: 74%
“…It would be therefore of interest to perform for example promoter capture Hi-C, both in hormone-deprived as well as hormone-stimulated prostate cancer cell lines to characterize the AR enhancer-target gene interactome along with the potential dynamics thereof. Very recently, AR-centered chromatin interactions in VCaP cells were mapped with ChIA-PET (Zhang et al 2019).…”
Section: How To Identify Ar Target Genes?mentioning
confidence: 99%